1993
DOI: 10.1021/bi00087a022
|View full text |Cite
|
Sign up to set email alerts
|

Transfer nuclear Overhauser effect study of the conformation of oxytocin bound to bovine neurophysin I

Abstract: This study reports the structure of the peptide hormone oxytocin bound to its carrier protein, neurophysin I, obtained by nuclear magnetic resonance techniques. At the pH value of 2.1 in our experiments, the ligand is in fast exchange with its carrier protein, allowing the use of transfer-NOE methods. The number of distance constraints for the peptide being limited, considerable attention has been paid to an accurate distance determination. The resulting accurate distance limits were used as input for a distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 64 publications
7
21
1
Order By: Relevance
“…The backbone chemical shifts of residues 7-9 are consistent with random coil values and were predicted to be dynamic by Talos þ 41 , in agreement with previous studies (region coloured in red in Fig. 5b) 38 . The unfavourable NMR properties of sulphur make disulphide bonds largely 'invisible' in NMR studies 42 ; in contrast, the SeCtt analogue provided structural constraints through 77 Se couplings to neighbouring methylenes while the additional methylene within the hydrophobic core 14 generated extra distance restraints.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The backbone chemical shifts of residues 7-9 are consistent with random coil values and were predicted to be dynamic by Talos þ 41 , in agreement with previous studies (region coloured in red in Fig. 5b) 38 . The unfavourable NMR properties of sulphur make disulphide bonds largely 'invisible' in NMR studies 42 ; in contrast, the SeCtt analogue provided structural constraints through 77 Se couplings to neighbouring methylenes while the additional methylene within the hydrophobic core 14 generated extra distance restraints.…”
Section: Resultssupporting
confidence: 90%
“…Later, NMR studies of OT were focused on its conformation when bound to neurophysin 37 . This latter study reported a lack of inter-residue dipolar connectivities in the absence of neurophysin, and subsequent studies have therefore assumed that OT is flexible and unstructured in solution 38 . This has led to the suggestion that binding to the OT receptor may occur through a receptor-induced fit 34 .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This is analogous to the amide proton of Phe 3 in our bound structure, which is directed to the inside of the 20-membered ring moiety. Similar observations were noted with the bound structure of oxytocin to neurophysin-I (6).…”
Section: Discussionsupporting
confidence: 83%
“…For ligands that bind weakly to the target (K d in the lM range) detailed structural information on the ligand bound conformation can be obtained by transferred-NOEs and transferred-CCR rates [1][2][3][4][5][6]. This approach requires small quantities of unlabeled target (1-10 lM solution) and an excess of ligand, is applicable to any complex independently of the size of the target macromolecule and does not require any isotope labeling scheme.…”
Section: Introductionmentioning
confidence: 99%